Connect with a community of experts and enthusiasts on IDNLearn.com. Join our community to receive timely and reliable responses to your questions from knowledgeable professionals.
Sagot :
Sure! Let's solve the equation [tex]\( x^2 - 14x + 49 = 1 \)[/tex] by completing the square.
1. Start with the given equation:
[tex]\( x^2 - 14x + 49 = 1 \)[/tex]
2. First, move the constant term from the right side to the left side:
[tex]\( x^2 - 14x + 49 - 1 = 0 \)[/tex]
Simplifying this, we get:
[tex]\( x^2 - 14x + 48 = 0 \)[/tex]
3. Notice that we can rewrite the left-hand side as a complete square. To do this, we take the coefficient of [tex]\( x \)[/tex], which is -14, divide it by 2, and square the result:
[tex]\( \left(\frac{-14}{2}\right)^2 = 7^2 = 49 \)[/tex]
4. Now, rewrite the quadratic expression as a perfect square:
Since [tex]\( x^2 - 14x + 49 = (x - 7)^2 \)[/tex], we can rewrite the equation:
[tex]\( (x - 7)^2 = 1 \)[/tex]
5. Next, solve for [tex]\( x \)[/tex] by taking the square root of both sides:
[tex]\( x - 7 = \sqrt{1} \)[/tex] or [tex]\( x - 7 = -\sqrt{1} \)[/tex]
6. Solve each of these equations separately:
- For [tex]\( x - 7 = 1 \)[/tex]:
[tex]\( x = 1 + 7 \)[/tex]
[tex]\( x = 8 \)[/tex]
- For [tex]\( x - 7 = -1 \)[/tex]:
[tex]\( x = -1 + 7 \)[/tex]
[tex]\( x = 6 \)[/tex]
7. Therefore, the solutions to the equation [tex]\( x^2 - 14x + 49 = 1 \)[/tex] are:
[tex]\[ x = 8 \quad \text{and} \quad x = 6 \][/tex]
So, the solutions to the equation are:
[tex]\[ x = 8 \text{ and } x = 6 \][/tex]
1. Start with the given equation:
[tex]\( x^2 - 14x + 49 = 1 \)[/tex]
2. First, move the constant term from the right side to the left side:
[tex]\( x^2 - 14x + 49 - 1 = 0 \)[/tex]
Simplifying this, we get:
[tex]\( x^2 - 14x + 48 = 0 \)[/tex]
3. Notice that we can rewrite the left-hand side as a complete square. To do this, we take the coefficient of [tex]\( x \)[/tex], which is -14, divide it by 2, and square the result:
[tex]\( \left(\frac{-14}{2}\right)^2 = 7^2 = 49 \)[/tex]
4. Now, rewrite the quadratic expression as a perfect square:
Since [tex]\( x^2 - 14x + 49 = (x - 7)^2 \)[/tex], we can rewrite the equation:
[tex]\( (x - 7)^2 = 1 \)[/tex]
5. Next, solve for [tex]\( x \)[/tex] by taking the square root of both sides:
[tex]\( x - 7 = \sqrt{1} \)[/tex] or [tex]\( x - 7 = -\sqrt{1} \)[/tex]
6. Solve each of these equations separately:
- For [tex]\( x - 7 = 1 \)[/tex]:
[tex]\( x = 1 + 7 \)[/tex]
[tex]\( x = 8 \)[/tex]
- For [tex]\( x - 7 = -1 \)[/tex]:
[tex]\( x = -1 + 7 \)[/tex]
[tex]\( x = 6 \)[/tex]
7. Therefore, the solutions to the equation [tex]\( x^2 - 14x + 49 = 1 \)[/tex] are:
[tex]\[ x = 8 \quad \text{and} \quad x = 6 \][/tex]
So, the solutions to the equation are:
[tex]\[ x = 8 \text{ and } x = 6 \][/tex]
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Thanks for visiting IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more helpful information.